Planning and Management of Village Funds for The Development of Cunca Wulang Tourism Village - Deliman, Ludgardis (Eastasouth Institute, 2023)
This study aims to identify and understand the system of planning and managing village funds for the development of tourist villages in Cunca Wulang. This type of research is descriptive type using primary and secondary data collected using observation, interview and documentation techniques. Data collection techniques were carried out by direct question-and-answer interviews with research informants, observations and interviews. The results of the research show that the planning and management of village funds is carried out in two stages by the Cunca Wulang village government. The first stage of village fund planning and management begins with the establishment of a village mid-term planning and management team (RPJMDesa). Formation of the RPJMDes planning team, preparation of the RPJMDesa and RKPDes documents so that they become the APBDes up to the preparation of the APBDes. In the second stage, the Cunca Wulang village government for tourism development has a tourism planning stage which is the most basic stage for the development of a tourist village. This planning stage involves the community in preparing plans so that the community can find out how to develop existing nature tourism, besides that they can feel the impact of the existence of a tourism village on the environment around the tour.